Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Pengguna Kereta Api Commuter Line Pada Kereta Api Commuter Line Arah Palmerah Ke Parungpanjang - Muhammad Dede Ramdhani; Nani Nani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - The purpose of this study is to determine the effect of service quality and facilities on the satisfaction of Commuter Line train users on the Palmerah to Parung Panjang route. The research method used is descriptive quantitative with a total sample of 100 respondents. Primary data were collected through questionnaires and processed using the SPSS application version 25. The data analysis methods used include validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of this study indicate that service quality has a positive and significant effect on user satisfaction with a coefficient of determination value of 55.9%, and the hypothesis test shows that the value of tcount > ttable (5.949 > 0.195) with a significance level of 0.000 < 0.05. Facilities have a positive but not significant effect on user satisfaction with a coefficient of determination value of 42.3%, and the hypothesis test shows that the value of tcount > ttable (1.770 > 0.195) or not significant with a significance value of 0.080 > 0.05. Service quality and facilities simultaneously have a positive and significant effect on user satisfaction with the regression equation Y = 3.459 + 0.542X1 + 0.162X2. The coefficient of determination value is 91.1%, while the remaining 8.9% is influenced by other factors not examined in this study. The hypothesis test shows that the value of Fcount > Ftable (68.095 > 3.09).